2020
DOI: 10.1039/d0ra06730j
|View full text |Cite|
|
Sign up to set email alerts
|

The inactivation mechanism of chemical disinfection against SARS-CoV-2: from MD and DFT perspectives

Abstract: Exploring effective disinfection methods and understanding their mechanisms on the new coronavirus is becoming more active due to the outbreak of novel coronavirus pneumonia (COVID-19) caused by severe acute respiratory coronavirus 2 (SARS-CoV-2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Tan et al have mentioned that chlorinated disinfectants, 75% ethanol, and heat showed effective inactivation of SARS-CoV-2. 30 Criscuolo et al also presented that ozone (4 ppm) exposure for 120 min led to 98.2%, 99.8%, 99.8%, 90%, and 93.3% viral titer reduction of SARS-CoV-2 on glass, gauze, sanitize fleece, plastic, and wood surface, respectively. While UV-C light (1.8 mW/cm 2 ) irradiation for 15 min displayed an absolute antiviral property (>99.9%) on glass, plastic, and gauze; 90% and 94.4% titer decrease on fleece and wool, respectively.…”
Section: Introductionmentioning
confidence: 96%
“…Tan et al have mentioned that chlorinated disinfectants, 75% ethanol, and heat showed effective inactivation of SARS-CoV-2. 30 Criscuolo et al also presented that ozone (4 ppm) exposure for 120 min led to 98.2%, 99.8%, 99.8%, 90%, and 93.3% viral titer reduction of SARS-CoV-2 on glass, gauze, sanitize fleece, plastic, and wood surface, respectively. While UV-C light (1.8 mW/cm 2 ) irradiation for 15 min displayed an absolute antiviral property (>99.9%) on glass, plastic, and gauze; 90% and 94.4% titer decrease on fleece and wool, respectively.…”
Section: Introductionmentioning
confidence: 96%
“…MEP maps created with computational methods estimate sites that are especially sensitive to electrophilic and nucleophilic interactions of molecular structures before molecular docking [103][104][105]. Software programs that researchers frequently use include AMBER, AVOGADRO, DMOL3, GAUSSIAN, HYPERCHEM, JAGUAR, and MOE [106][107][108][109][110][111][112][113][114].…”
Section: Computer Aided Drug Designmentioning
confidence: 99%
“…The emergence of SARS-CoV-2 virus has become a serious threat to public health. 1 Since the end of 2019, the world has been trying to control the pandemic outbreak caused by COVID-19 disease, which as of September 14, 2021, had caused 4,547,782 deaths in 219,456,675 cases of infection. 2 Identified in 1960, coronaviruses are a family of viruses that naturally reside in animals, mainly in some species of bats.…”
Section: Introductionmentioning
confidence: 99%
“…11 These products available on the market are effective in a very short space of time due to their high rate of evaporation, corrosivity, and immediate action, implying frequent applications on surfaces to be disinfected. 1 Due to this fact, there is a market need to develop new materials that maximize the action of these disinfecting agents to prolong the sterilization time and reduce the need and frequency of their application by the end-user. Microencapsulation appears as an alternative to overcome this limitation.…”
Section: Introductionmentioning
confidence: 99%